2020
DOI: 10.1002/acr.24073
|View full text |Cite
|
Sign up to set email alerts
|

What Does the Patient Global Health Assessment in Rheumatoid Arthritis Really Tell Us? Contribution of Specific Dimensions of Health‐Related Quality of Life

Abstract: Objective. To estimate the contributions of health-related quality of life domains to the patient global assessment of health (PtGA) in rheumatoid arthritis (RA). Methods. Data are drawn from baseline visits of 2 observational RA cohorts. Participants completed patientreported outcome measures, including PtGA and Patient-Reported Outcomes Measurement Information System measures, and clinical data were collected. Factor analysis was used to identify latent variables, and multivariable linear regression was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…This is, therefore, not the reason "why high patient global assessment scores, even when 28-joint counts are low, identify patients at high risk of later functional loss" (1). This may be simply and better explained by the fact that function is a major determinant of PGA, irrespective of (inflammatory) disease activity, as repeatedly reported (5,6,8,13). These publications are the basis of our dual target strategy proposal, which we hypothesize may result in more accurate and comprehensive definitions of remission.…”
Section: To the Editormentioning
confidence: 60%
“…This is, therefore, not the reason "why high patient global assessment scores, even when 28-joint counts are low, identify patients at high risk of later functional loss" (1). This may be simply and better explained by the fact that function is a major determinant of PGA, irrespective of (inflammatory) disease activity, as repeatedly reported (5,6,8,13). These publications are the basis of our dual target strategy proposal, which we hypothesize may result in more accurate and comprehensive definitions of remission.…”
Section: To the Editormentioning
confidence: 60%
“…Such variation in how people interpret the PtGA has been described in a mixed-methods study of 33 patients with RA, which reported that patients considered their pain, fatigue, function and psychological well-being, with comorbidities and RA sequelae also influencing scoring [ 30 ]. Other studies using quantitative approaches also demonstrate strong associations between PtGA and function, emotional distress and social participation [ 7 , 8 , 31 ]. In addition, the relationship between pain intensity and PtGA scores reflects previous research on the subjective components of disease activity scores by McWilliams and colleagues [ 32 ].…”
Section: Discussionmentioning
confidence: 86%
“…This is, therefore, not the reason ‘why high patient global assessment scores, even when 28-joint counts are low, identify patients at high risk of later functional loss’ 1. This may be simply and better explained by the fact that function is a major determinant of PGA, irrespective of (inflammatory) disease activity, as repeatedly reported 5 6 8 13. These publications are the basis of our ‘Dual Target Strategy’ proposal, which we hypothesise, may result in more accurate and comprehensive definitions of remission.…”
mentioning
confidence: 94%